Moral values as the basis for the formation of a multicultural personality - Куздеубаева, Алия; Мустапаева, Талшын; Тобағабылова, Айжан (Pedagogy and Psychology, 2021)
The article considers moral values as guidelines that determine the effectiveness of the formation of a multicultural personality. The pedagogical conditions for the implementation of the model of the formation of a multicultural personality based on moral values in a multiethnic educational space are revealed, the relevance of the issues of spiritual and moral education in a modern school is substantiated. The purpose of the study is to identify the socio-pedagogical conditions of spiritual and moral education of students, taking into account the specifics of the multicultural educational environment. The content of the concepts "spiritual and moral education", "educational environment", "multicultural environment", "regional cultural and educational environment" is considered on the basis of an interdisciplinary analysis of the works of Kazakhstani scientists on the stated problems. Structural components are classified, indicators are determined and levels of formation of spiritual and moral education of students are described. The unity of Kazakhstan’s society is determined by traditions and spiritual and moral values common to different generations. Education is one of the main indicators of the development of society.